Pengaruh Pelatihan Terhadap Produktivitas Kerja Karyawan PT. Bank Danamon Cabang Kendari - Adan, Ingrid Ayu Lestari; Utha, Arifin; Mustakim, Mustakim (Universitas Halu Oleo, 2021)
The purpose of this study was to determine the effect of training on the work productivity of PT. Bank Danamon Cabang Kendari. The population in this study were employees of PT. Bank Danamon Cabang Kendari, as many as 30 people. The sample in this study was determined by a census sample where the sampling method was if all of the sample population was 30 employees. The method used in this research is descriptive quantitative. The results in this study indicate that training from the dimensions of 1) training objectives, 2) training participants, 3) training materials, 4) training methods, has a significant effect on work productivity. Then based on the results of the analysis of the effect of training on the work productivity of PT. Bank Danamon Cabang Kendari, shows that the effect of training is 66% and the remaining 34% is caused by other variables outside of this study. Then the dimensions of employee training at PT. Bank Danamon Cabang Kendari which provides the highest reflection on work productivity is the dimension of training objectives. While the dimensions of employee training at PT. Bank Danamon Cabang Kendari, which provides the lowest reflection on work productivity is the quality dimension.